Diazotrophic growth of free-living Rhizobium etli: Community-like metabolic modeling of growing and non-growing nitrogen-fixing cells. - Maryam Afarin; Fereshteh Naeimpoor (PLoS ONE)
Rhizobium etli, a nitrogen-fixing bacterium, grows both in symbiosis (with plants) and in free-living state. While most metabolic models focus on its symbiotic form, this study refined the existing iOR363 model to account for free-living growth. By addition of a biomass formation reaction followed by model curation growth was simulated using various N-sources (NH₃, NO₂, and NO₃). At fixed succinate uptake rate (4.16 mmol/gDWC/h), ammonia yielded the highest growth rate of 0.259 h ⁻ ¹. To represent free-living N-fixing R. etli, a novel two-member community-like model, consisting of both growing and differentiated non-growing N-fixing cells with ammonia exchange, was developed. The XFBA approach, based on community Flux Balance Analysis (cFBA), was formulated to maintain fixed abundances rather than assuming equal growth rates. With a non-growing:growing abundance ratio of 1:9 in community, N-fixation resulted in lower growth rate of 0.1933 h ⁻ ¹ due to the high energy demand of N₂ assimilation compared to ammonia. Sensitivity analysis revealed that increased abundance of N-fixing cells from 5 to 30% led to decreases of 10% in N2-fixation and 25% in growth rate of growing member. Furthermore, Principal Component Analysis identified oxidative phosphorylation, TCA cycle, and glycolysis as key pathways differentiating flux distributions across N-sources. At high uptake of oxygen, causing nitrogenase inactivity, cytochrome bd oxidase was activated to scavenge oxygen, though at the cost of lower growth rate (by 12% per mmol increase in O2 uptake/gDWC/h). This study provided a platform to obtain insights to free-living state of R. etli which may have applications for other diazotrophs.